Pembatalan Perkawinan Tanpa Persetujuan Orang Tua sebagai Wali Nasab (Studi Putusan Pengadilan Agama Medan No. 2530/Pdt.G/2019/PA.Mdn) - Devia Sutanri Nasution; Hasballah Thaib; Zamaksyari Bin Hasballah Thaib (Jurnal Smart Hukum (JSH), 2022)
The problem of this research, related to marriage without the consent of the guardian of the lineage can be canceled. legal consequences after the marriage was annulled without the permission of the lineage guardian and the judge's legal considerations in the Medan Religious Court Decision No. 2530/Pdt.G/2019/PA.Mdn. This study uses literature research and empirical research at the Medan Religious Court by conducting interviews with two judges. The results of the study that marriages without the consent of the nasab guardian can be canceled, this is in accordance with the provisions of Article 22 of Law Number 1 of 1974 which states "Marriage can be annulled, if the parties do not meet the requirements to carry out the marriage". In other words, if the conditions for a marriage are not met, the marriage can be annulled. The reasons that can be submitted for the annulment of a marriage. A marriage that is held in the presence of an unauthorized marriage registrar and a marriage guardian who performs the marriage is invalid or without the approval of the lineage guardian. The legal consequences after the marriage is annulled without the permission of the lineage guardian, first, the termination of the marital relationship between Defendant I and Defendant II, so that the marriage is considered to have never existed. Second, Defendant II as a father is obliged to provide a living for children who have been born from the marriage. This is in accordance with Article 45 paragraph (1) of the Marriage Law which stipulates that both parents are obliged to maintain and educate their children as well as possible. Third, regarding the position of joint property where the distribution of joint property is handed over to each party in accordance with the agreement of each party. Regarding the distribution of joint property, joint property must be divided equally. The judge's legal considerations relate to the annulment of the marriage in accordance with the applicable legal provisions, and for the benefit of the people, even though there are losses from both parties whose marriage is annulled.